PENCEGAHAN FRAUD PENGADAAN BARANG DAN JASA DI PEMERINTAH DKI JAKARTA: Telaah penerapan e-procurement dan pengendalian internal - Alifka Ajeng Suseno, (2022)
Electronic/online goods and services procurement or well known as e-procurement systems are implied by the government to actualize good governance by enhancing internal control systems and tightening fraud prevention systems through the government budget's absorption process. This research aims to examine and prove the effect of e-procurement implication and internal control towards fraud prevention on goods/services procurement and the implication towards the government's capital expenditure budget absorption. The population of this research is those who are involved in goods/services procurement at Local Government Work Unit (SKPD) of South Jakarta and West Jakarta, Province Government Work Unit of Jakarta Special Region, and Indonesian Ministry of Agriculture. This research obtains 69 respondents selected using purposive sampling method. The hypothesis in this study was tested using Structural Equation Modelling (SEM) using software SmartPLS 3,0. The result of study shows that e-Procurement implication and internal control have significant effects towards fraud prevention and government's budget absorption. Meanwhile, government's capital expenditure budget absorption has no significant influence towards fraud prevention in goods/services procurement. The implication of capital expenditure budget absorption is not able to mediate/moderate the effect of e-Procurement towards fraud prevention on goods/service procurement.